An improvement of the sales administration process performance; A case study at Guthrie Property Development Holding Berhad (GPDH), Bukit Jelutong Shah Alam / Mazhayu Limat - Limat, Mazhayu (Faculty of Business and Management, 2007)
Guthrie Property Development Holdings Berhad (GPDH) has made a move from Kumpulan Guthrie Berhad, venturing into property development in 1994 through a 55 per cent stake. GPDH was awarded ISO 9001:2000 certification from SIRIM QAS International Sdn. Berhad. The achievement paves the way for recognition of a quality builder status and to maintain their quality of management performance, they need to improve their process performance to ensure they can achieve the ISO objective. The purpose of this project paper is to study on improving performance of the Sales Administration process to overcome some common weaknesses where they are having problems while receiving the Sales and Purchase Agreement (SPA), getting authorized signatories and collecting 10% balance of payment within three months. This project paper proposed three behavioral indicators for process performance which includes time management, team productivity and team working of organizational as the key to improve performance. Data being collected by questionnaire, telephone calls interviews and also observation in the Sales Office of Guthrie Property Development Holding and Project Development Office. Thus further studies being done to find the way Of improving the Sales Administration Processes.